Tolvaptan Add-on Therapy to Overcome Loop Diuretic Resistance in Acute Heart Failure With Renal Dysfunction (DR-AHF): Design and Rationale - Minh, Nhat Giang; Hoang, Hai Nguyen; Maeda, Daichi; Matsue, Yuya (Frontiers in Cardiovascular Medicine, 2022)
Background Diuretic Resistance in Acute Heart Failure (DR-AHF) was designed to demonstrate the effectiveness of the early tolvaptan (a vasopressin-2 receptor antagonist) add-on therapy in patients with AHF with renal dysfunction and to provide clinical evidence of loop diuretic resistance. Methods and Results This single-centered, open-labeled, randomized, and controlled trial enrolled 128 patients hospitalized with AHF, as participants. These patients with a wet-warm phenotype, whose estimated glomerular filtration rates are of ≥15 ml/min/1.73 m2 and ≤ 60 ml/min/1.73 m2, with a cumulative urine output of <300 ml 2 h after the first dose of intravenous furosemide, will be randomly assigned 1:1 to receive standard care with an uptitrating intravenous furosemide alone, or a combination therapy with 15 mg of tolvaptan administered once daily for 2 days. The standard furosemide treatment will follow the latest position statements of the Heart Failure Association. The primary endpoint is the cumulative urine output at 48 h. The key secondary endpoints include the improvement of fractional excretion of sodium at 6 h, the total dose of furosemide, and the incidence of worsening renal function (WRF) at 48 h. Conclusions Although the combination of diuretic treatment has recently gained more attention due to its physiologically synergistic action, its advantages may be outweighed by the substantial risk of electrolyte disturbances and severe WRF. Further, there is no consensus on the time point for early starting of add-on therapy and for the preferred diuretic combination. Trial registration NCT04331132.